Activity of the photosynthetic apparatus and productivity of transgenic winter wheat plants with partial suppression of the proline dehydrogenase gene - Galyna Priadkina; Oksana Dubrovna; Serhiy Sytnyk; Maksym Tarasiuk (Біологічні студії)
Background. Partial suppression of the proline dehydrogenase (ProDH) gene in transgenic winter wheat plants leads to an increase in the level of free proline accumulation. However, the effect of increasing the content of this amino acid on the physiological and biochemical characteristics of this crop is still not fully understood. In this regard, the aim of the work was a comparative analysis of the influence of the free proline accumulation on the activity of the photosynthetic apparatus parameters of transgenic wheat plants at reproductive period under variable weather conditions, as well as on their productivity. Materials and Methods. The study involved non-transformed winter bread wheat plants of genotype UK 997/19 and transgenic lines of seed generation T2 obtained on their basis. The content of free proline, photosynthetic pigments and parameters of the photosynthetic apparatus activity were determined. The analysis of the elements of the crop structure was carried out at full ripeness. Results. Under conditions of increased air temperature or lack of moisture in the soil, it was established that the total chlorophyll content in the leaves of plants of the transgenic lines at milk-wax maturity exceeded its level in the wild-type plants by 15.9–32.5 %. At this phase, they had a higher effective quantum yield (ϕPSII) by 16–28 %, the coefficient of photochemical quenching (qP) by 23–26 % and the fraction of open reaction centers (qL) by 28–61 % of photosystem II (PSII). No specific regularities were found in the changes in the non-photochemical quenching parameter (NPQ) in the antenna complexes of PS II leaves of the transgenic plants relative to the wild-type ones. The grain yield of plants of the modified lines was higher than that of the wild type. A significant positive correlation was found between the grain productivity of the transgenic plants with the fraction of open reaction centers of PSII, the effective quantum yield and photochemical quenching of fluorescence parameter (the coefficient of determination of the relationship varied from 0.762 to 0.966). Conclusions. The study results indicate that the elongation of the functioning of the flag leaf during the reproductive period and the higher activity of the photosynthetic apparatus in the transgenic wheat lines with an increased proline content under the conditions of increased air temperature or lack of moisture in the soil contributed to an increase of their grain productivity.